Length-weight relationships of four fish species from the upper Parana River basin, Southeastern Brazil - Azevedo-Santos, V. M. [UNESP]; Coelho, P. N. [UNESP]; Brambilla, E. M. [UNESP]; Lima, F. P. [UNESP]; Nobile, A. B. [UNESP]; Britton, J. R. (Wiley-Blackwell, 2018)
Here the length-weight relationships (LWR, hereafter) of Pareiorhina pelicicei, Trichomycterus candidus, T.pirabitira, and T.piratymbara are provided. Samples of each species were collected between April and July 2017 with a hand net (1.5mm mesh) in three sites from the upper Parana River basin, Southeastern Brazil. These results increase knowledge about the LWR of Neotropical freshwater fish.